Constructing a Reliable and Valid Instrument to Measure Post-Secondary Studentsa Cultural Competence (Global Journal of Human-Social Science, 2018)
Institutions of Higher Education must understand and engage with students perceptions of diversity within the social and academic contexts of campus life Diversity pluralism equity access multiculturalism regardless of how they have been named have been on the agenda of colleges and universities for nearly 50 years Pope Mueller Reynolds 2009 p 640 Toward this end researchers have developed cultural competence instruments for teachers counselors and student affairs professionals Cheng Zhao 2006 For our study we define cultural competence as knowledge of and sensitivity to the accumulated store of symbols ideas and material products associated with multiple group experiences The groups will be those identified by race ethnicity gender sexual orientation religion language and ability disability Additionally awareness of one s own identity and membership in the various groups mentioned above is a critical component of cultural competence